2014
DOI: 10.1038/gt.2014.102
|View full text |Cite
|
Sign up to set email alerts
|

SPARC (secreted protein acidic and rich in cysteine) knockdown protects mice from acute liver injury by reducing vascular endothelial cell damage

Abstract: Secreted protein, acidic and rich in cysteine (SPARC) is involved in many biological process including liver fibrogenesis, but its role in acute liver damage is unknown. To examine the role of SPARC in acute liver injury, we used SPARC knock-out (SPARC−/−) mice. Two models of acute liver damage were used: concanavalin A (Con A) and the agonistic anti-CD95 antibody Jo2. SPARC expression levels were analyzed in liver samples from patients with acute-on-chronic alcoholic hepatitis (AH). SPARC expression is increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Previous results showed that Smoc2 plays an important role in promoting G1/S progression through participating in the maintenance of cyclin D1 expression[34-36]. In other words, cyclin D1 can be considered as an effector of Smoc2-induced DNA synthesis[37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that Smoc2 plays an important role in promoting G1/S progression through participating in the maintenance of cyclin D1 expression[34-36]. In other words, cyclin D1 can be considered as an effector of Smoc2-induced DNA synthesis[37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Liver damage of different causes induces secreted protein, acidic and rich in cysteine (SPARC) expression [15]. SPARC has the ability to induce a positive feedback with transforming growth factor beta (TGF-β)-1, stimulates collagen deposition, induces inflammation, and has anti-proliferative properties.…”
Section: Introductionmentioning
confidence: 99%
“…SPARC has the ability to induce a positive feedback with transforming growth factor beta (TGF-β)-1, stimulates collagen deposition, induces inflammation, and has anti-proliferative properties. We have previously demonstrated that downregulation of SPARC has the capacity to reduce acute liver damage after concanavalin A (ConA) administration [5], and the degree of fibrosis in tioacetamide (TAA) and bile duct ligation models [5, 4]. The mechanistic role of SPARC in liver pathologies has not been addressed, although our previous works demonstrated that SPARC −/− mice treated with ConA showed reduction in T CD4 + lymphocytes infiltration, tumor necrosis factor alpha (TNFα) production, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS generation is a key regulator of liver IRI and was until recently viewed as the primary driver for parenchymal cell death during IRI, but more recent studies demonstrate that ROS is cytoprotective through its activation of the cellular process of autophagy . Indeed, autophagy activation has been shown to limit injury following a variety of acute liver injuries, and its role in regulating liver IRI is attracting growing attention . Limited studies have explored the role of ROS‐dependent autophagy during IRI, but the relationship between ROS and autophagy in LEC during IRI is not known.…”
Section: Discussionmentioning
confidence: 99%